2016
DOI: 10.1093/ofid/ofw169
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Norovirus Infection Among Immunocompromised Patients at a Tertiary Care Research Hospital, 2010–2013

Abstract: Background. Noroviruses are a major cause of infectious gastroenteritis worldwide, and viruses can establish persistent infection in immunocompromised individuals. Risk factors and transmission in this population are not fully understood.Methods. From 2010 through 2013, we conducted a retrospective review among immunocompromised patients (n = 268) enrolled in research studies at the National Institutes of Health Clinical Center and identified a subset of norovirus-positive patients (n = 18) who provided stool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
(46 reference statements)
1
9
1
2
Order By: Relevance
“…Remarkably, the parents had not presented a norovirus infection during the study period, and yet, the viral loads in the chronic patient were equivalent to those found in acute infections. On the other hand, a recent study has also shown that chronically infected patients had not transmitted noroviruses to other individuals (19). These results suggested that chronic noroviruses might not maintain a pathogenesis similar to that of other GII.4 noroviruses circulating in the community, as suggested with other viruses (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the parents had not presented a norovirus infection during the study period, and yet, the viral loads in the chronic patient were equivalent to those found in acute infections. On the other hand, a recent study has also shown that chronically infected patients had not transmitted noroviruses to other individuals (19). These results suggested that chronic noroviruses might not maintain a pathogenesis similar to that of other GII.4 noroviruses circulating in the community, as suggested with other viruses (36).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have speculated that these chronically infected individuals might even function as reservoirs for the generation of novel noroviruses that could be transmitted into the community and escape the herd immunity (17, 18). On the other hand, a recent molecular epidemiological analysis of chronically infected patients found no evidence for this kind of transmission (19). Therefore, the idea of a reservoir(s) for novel strains and the transmissibility of chronic noroviruses are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…One of 10 patients (1%) or 3 of 50 (0.6%) fecal samples were positive for NVs, lower than a previously report (10%) in hematological malignancies (Bok et al, 2016). This may be related to the short time of sample collection and the small number of samples collected in this study.…”
Section: Discussioncontrasting
confidence: 76%
“…We observed temporal trends that were consistent with prior studies that showed more infections occurring during the first quarter of the year when air temperatures are lower [ 43 ], but we also noted that >2% of patients experienced norovirus infections from September all the way until May, indicating an extended season of norovirus infections in our patient population. It is interesting to consider to what extent this supports the idea that immunocompromised populations could act as a viral reservoir for emergent strains [ 9 , 44 , 45 ], particularly those that occur off-season, or whether these infections merely represent introductions of viruses from the community [ 44 , 46 ]. Future longitudinal studies of norovirus infections in large cohorts of both immunocompromised and healthy individuals within a community would help shed light on this important question.…”
Section: Discussionmentioning
confidence: 99%